High-dose leucine supplementation does not prevent muscle atrophy or strength loss over 7 days of immobilization in healthy young males. Issue 5 (10th September 2020) - Edwards, Sophie J; Smeuninx, Benoit; Mckendry, James; Nishimura, Yusuke; Luo, Dan; Marshall, Ryan N; Perkins, Molly; Ramsay, Jill; Joanisse, Sophie; Philp, Andrew; Breen, Leigh
ABSTRACT: Background: Unavoidable periods of disuse lead to muscle atrophy and functional decline. Preventing such declines can reduce the risk of re-injury and improve recovery of normal physiological functioning. Objectives: We aimed to determine the effectiveness of high-dose leucine supplementation on muscle morphology and strength during 7 d of unilateral lower-limb immobilization, and the role of myofibrillar (MyoPS) and mitochondrial (MitoPS) protein synthesis in disuse atrophy. Methods: Sixteen healthy males (mean ± SEM age: 23 ± 1 y) underwent 7 d of unilateral lower-limb immobilization, with thrice-daily leucine (LEU; n = 8) or placebo (PLA; n = 8) supplementation (15 g/d). Before and after immobilization, muscle strength and compartmental tissue composition were assessed. A primed continuous infusion of l -[ring- 13 C6 ]-phenylalanine with serial muscle biopsies was used to determine postabsorptive and postprandial (20 g milk protein) MyoPS and MitoPS, fiber morphology, markers of protein turnover, and mitochondrial function between the control leg (CTL) and the immobilized leg (IMB). Results: Leg fat-free mass was reduced in IMB (mean ± SEM: −3.6% ± 0.5%; P = 0.030) but not CTL with no difference between supplementation groups. Isometric knee extensor strength declined to a greater extent in IMB (−27.9% ± 4.4%) than in CTL (−14.3% ± 4.4%; P = 0.043) with no difference between groups. In response to 20 g milk protein, postprandial MyoPS rates were significantly lower in IMB than in CTL (−22% ± 4%; P < 0.01) in both LEU and PLA. Postabsorptive MyoPS rates did not differ between legs or groups. Postabsorptive MitoPS rates were significantly lower in IMB than in CTL (−14% ± 5%; P < 0.01) and postprandial MitoPS rates significantly declined in response to 20 g milk protein ingestion (CTL: −10% ± 8%; IMB: −15% ± 10%; P = 0.039), with no differences between legs or groups. There were no significant differences in measures of mitochondrial respiration between legs, but peroxisome proliferator–activated receptor γ coactivator 1-α and oxidative phosphorylation complex II and III were significantly lower in IMB than in CTL ( P < 0.05), with no differences between groups. Conclusions: High-dose leucine supplementation (15 g/d) does not appear to attenuate any functional declines associated with 7 d of limb immobilization in young, healthy males. This trial was registered at clinicaltrials.gov as NCT03762278.